BIBLICAL IMAGE OF TRUE SONSHIP IN THE EPISTLE TO THE HEBREWS - Shumilin, Alexander (Skhid, 2020)
The theme of sonship is one of the central themes in the New Testament. Sometimes it can be traced explicitly, but more often indirectly. True sonship involves obedience to parents and, as a result, leads to parental blessing. This is the truth the writer of the Epistle to the Hebrews wanted to convey to his readers. He did this using the example of Jesus Christ as the only begotten Son of God. He, being the true the Son, consubstantial to Father, showed complete and unconditional obedience, despite the strongest temptations and incredible suffering. His obedience to the Father not only led Him to glory, not only showed the holy essence and wisdom of God Himself, but also led and leads to the glory of His followers. Called by God and saved by Him, having become His children, in obedience to God, must become like the Son of God, as the Firstborn. Only a consecrated life leads one to blessings. The foundation of such a life is faith in Jesus Christ and living according to His commandments. Apostasy from Him and transgression of God’s commandments deprives a person of blessing and grace. Most scholars of the Epistle to the Hebrews place more emphasis on the Sonship of Christ and His High Priesthood, and this is important to show the members of the community the superiority of what they have in Jesus over Judaism. However, there are few who emphasize the obedience of the Son of God to His Heavenly Father and its consequences, as well as an example of this obedience for followers of Jesus Christ. The author of the Epistle wants to show that not only the confession of Jesus Christ as Lord, but also obedience is a guarantee of blessing. It was the disobedience of the community members that led them to God’s punishment, caused a crisis of faith, and led to apostasy. A true son is an obedient son. If there are any mentions of Christ’s obedience and His example for His followers in the studies of various authors, then they are very short and local. Therefore, the task of this study is a deeper study of the Epistle within the framework of this topic.